Spatial-temporal Evolution of the Normalized Difference Vegetation Index (NDVI) in the Huaihe River Basin from 1999 to 2018 - GAO Zheng; LIU Saiyan; QIN Xuan; XU Liuxin (Renmin Zhujiang)
Vegetation is one of the main participants in the global carbon cycle and plays an important role in land surface water transport and energy transmission.Based on the normalized difference vegetation index (NDVI) of the Huaihe River Basin (HRB) from 1999 to 2018,the spatial-temporal evolution law of NDVI was studied on three time scales (month,quarter,and year) through the Mann-Kendall trend test and empirical orthogonal function (EOF) decomposition.The following findings are obtained.① Affected by crop maturity and different landforms,the multi-year average values of monthly NDVI in the HRB present an M-shaped distribution as a whole,and there are some differences in the mean value and variation range of NDVI in different sub-basins.② In the downstream area with more farmlands,the NDVI shows an insignificant downward trend in summer and winter,while in other three sub-basins of the river,the NDVI follows an upward trend in all seasons,especially in spring and autumn.③ The annual NDVI of the basin exhibits a significant upward trend,which is the same as the global greening trend.This also indicates that returning cropland back to forests and other soil and water conservation measures have achieved remarkable results in vegetation restoration and ecological protection in the basin for the past 20 years.④ The spatial distribution of NDVI modes in the HRB shows simultaneous increases or decreases overall,with a great difference existing between the western and eastern areas.Vegetation coverage gradually decreases from inland to coastal.These research results can provide a reference basis for understanding the vegetation restoration characteristics and protecting the ecological environment in the HRB.